2010
DOI: 10.1007/s11302-010-9206-7
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotides affect neurogenesis and dopaminergic differentiation of mouse fetal midbrain-derived neural precursor cells

Abstract: The fetal midbrain is a preferred source for isolating and producing dopaminergic neurons for subsequent grafting and replacement of damaged or lost dopaminergic midbrain neurons. We analysed the potential of a variety of nucleotides and of adenosine to support dopaminergic neuron formation from primary mouse fetal midbrain-derived cells, harvested at E10.5 and at E13.5 and subjected to adherent cell culture. In contrast to cells derived at E13.5, cells derived at E10.5 have the potential to produce dopaminerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…Transplanting enteric nerves (containing dopaminergic nerves) may be a promising alternative (Tew et al, 1992). Nucleotides affect neurogenesis and have the potential to produce dopaminergic neurons from neural progenitor cells derived from foetal mouse midbrain (Delic and Zimmermann, 2010).…”
Section: Parkinson's Disease (Pd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Transplanting enteric nerves (containing dopaminergic nerves) may be a promising alternative (Tew et al, 1992). Nucleotides affect neurogenesis and have the potential to produce dopaminergic neurons from neural progenitor cells derived from foetal mouse midbrain (Delic and Zimmermann, 2010).…”
Section: Parkinson's Disease (Pd)mentioning
confidence: 99%
“…It has been reported that stem cell activation and the integration of newly formed neurons can be applied for neuroregeneration in the diseased brain (Martino and Pluchino, 2006;Ormerod et al, 2008;Delic and Zimmermann, 2010). Neural pluripotent precursor cells derived from primary neural stem cells proliferate to form the three main cell types constituting the neurons, astrocytes and oligodendrocytes, while microglia are derived from immune-like cells.…”
Section: Neuroregeneration: Neural Stem/progenitor Cellsmentioning
confidence: 99%
“…An embryonic mouse neural stem‐cell line (P2Y1,2; P2X1,2; Heo and Han, ) and fetal midbrain‐derived NPCs (P2Y1,2,4,6,12‐15; P2X1‐7; Delic and Zimmermann, ) both contained mRNA for a range of P2Rs. Primary neurospheres prepared from the SVZ of mice expressed only P2X4,7R mRNA as well as mRNA for all P2YR subtypes (Stafford et al, ).…”
Section: P2y and P2xr Messengersmentioning
confidence: 99%
“…Neuronal progenitors, isolated from midbrain of E10.5 mice, possess all components of the purinergic signalling system. mRNA for adenosine, P2X and P2Y receptors and ectonucleotidases are expressed, and stimulation of purinoceptors elicited neuronal formation [301]. P2X3, P2X4, P2Y 1 and P2Y 4 receptor expression was high in embryonic P19 cells but then decreased following induction of differentiation [302].…”
Section: Stem Cellsmentioning
confidence: 99%